Posibilidades de la expresión: los problemas del lenguaje en la obra narrativa de Alejandra Pizarnik - Torres Zuluaga, María Guadalupe (2019)
The present article describes the language problems manifested by Alejandra Pizarnik (Argentina, 1936-1972) in her literary work until they reach the peak of these: the prose text La bucanera de Pernambuco o Hilda la polígrafa, which is transcendent by her singular style that breaks the molds of contemporary writers to her in Latin America. The inefficiency of the language to describetheir designata exposed in this and other texts will be endorsed by the critical comments from some of her scholars: Vizcaíno, Piña, Venti, Negroni, among others. We affirm that La bucanera… is a proposal of “chaotic” encoding as a reaction to the loss of power suffered by language. This situation is the guiding thread of the entire Pizarnikian work.